Infectious Complications of Expanded Endoscopic Transsphenoidal Surgery: A Retrospective Cohort Analysis of 100 Cases - Lee, Seung J.; Cohen, Justin; Chan, Julie; Walgama, Evan; Wu, Arthur; Mamelak, Adam N. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective To identify perioperative factors that may predict postoperative cerebrospinal fluid (CSF) leak and meningitis following expanded endoscopic transsphenoidal surgery (EETS).Study Design This is a retrospective study. This study was set at the Cedars-Sinai Medical Center, Los Angeles. A total of 78 patients who underwent EETS between January 2007 and November 2018 were participated. The main outcome measures were CSF leak and meningitis.Results A total of 78 patients underwent a total of 100 EETS procedures; 17.9 and 10.3% of patients developed postoperative CSF leaks and meningitis, respectively. Out of eight, three patients with meningitis did not develop an observable CSF leak. The risk of developing meningitis in patients with a CSF leak was significantly higher than those without a leak, with an odds ratio (OR) of 11.48 (95% confidence interval, 2.33–56.47; p = 0.004). Pituicytomas were significantly associated with meningitis compared with other pathologies. No other patient-specific factors were identified as risks for leak or meningitis, including method of skull base repair, sex, tumor volume, or body mass index, although there was a strong trend toward reduced CSF leak rates in patient with nasoseptal flaps used for skull base repair, compared with those without (9.5 vs. 25%). CSF protein was consistently elevated on the first CSF values obtained when meningitis was suspected.Conclusion CSF leak and meningitis are common complications of expanded endonasal surgery No statistically significant risk factors for developing a postoperative leak other than the pathology of pituicytoma were identified, including method of skull base repair, although the use of a vascularized nasoseptal flap did trend toward a reduced CSF leak rate. CSF protein is the most sensitive marker for the presumptive diagnosis and timely treatment of meningitis.
Keywords: complication; CSF leak; expanded endoscopic transsphenoidal; infection; meningitis